2017
DOI: 10.5597/00226
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of bottlenose dolphins (Tursiops truncatus) in the Río Negro Estuary, Argentina, and their mid-distance movements along the northeastern Patagonian coast

Abstract: A systematic study was carried out on bottlenose dolphins (Tursiops truncatus) in the Río Negro Estuary (RNE), Patagonia, Argentina, to analyze their occurrence and activity patterns in this region. The photo-identification data of this study was further compared to data from an adjacent region to gain information on the animals' movements along the northeastern Patagonian coast. Information was gathered through land-based observations between the months of March and July of 2008 up to 2011. Data on dolphin ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Group size and composition (see also Table 2) In El Cóndor, Failla et al (2016) found that most groups observed contained 1-5 individuals (37%), although occasional aggregations of up to 20 dolphins (2% of groups) were recorded. The authors further reported that 31% of the observed groups contained calves, but never more than one calf per group.…”
Section: Residency and Ranging Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group size and composition (see also Table 2) In El Cóndor, Failla et al (2016) found that most groups observed contained 1-5 individuals (37%), although occasional aggregations of up to 20 dolphins (2% of groups) were recorded. The authors further reported that 31% of the observed groups contained calves, but never more than one calf per group.…”
Section: Residency and Ranging Patternsmentioning
confidence: 99%
“…1990-2016 (Fig. 2C): Despite the general presence of coastal bottlenose dolphins in the area for the past decades, dedicated studies only commenced in 2006, documenting the presence of a resident community ranging from Bahía San Antonio to El Cóndor (Vermeulen and Cammareri, 2009b;Vermeulen et al, 2016;Failla et al, 2016). In this area, 13 strandings were recorded between 2001 and 2015 (E. Vermeulen and M. Failla, pers.…”
Section: Río Negro Distribution and Occurrencementioning
confidence: 99%
“…Although no precise abundance estimates are available in this region specifically, the numbers are believed to be low based on photo-identification data for the time period 2010-2016, not exceeding 50 individuals (Vermeulen et al 2017). In the province of Río Negro, abundance was estimated at 83 (95% CI = 73 to 112) Lahille's Bottlenose Dolphins in Bahía San Antonio between 2009 and 2011 (using mark-recapture data and Pollock's Robust Design; Vermeulen and Bräger 2015), ranging at least along the entire coast of the San Matias Gulf (Failla et al 2016, Coscarella et al 2016. Based on a viability analysis, numbers were estimated to be declining at a rate of 1.1% per year during the study period 2009 to 2011 due to a low recruitment rate related to a low number of reproducing females (Vermeulen and Bräger 2015).…”
Section: Argentina Subpopulationmentioning
confidence: 99%